Rene Descartes ve John Locke’un zihin anlayaşılarının kıyaslanması - Boyraz, Kürşat (My University, 2004)
İnsan, düşünen zihinli bir varlıktır. O, bu yönüyle diğer canlılardan ayrılır. Zihnin ne olduğu, nasıl çalıştığı insanlık tarihi ve bilhassa felsefede ilkçağlardan beri tartışıla gelmiştir. Bu sayede felsefe tarihinde değişik düşünce akımları oluşmuş, insanlığı bu düşünceler etrafında sürüklemiştir. bu çalışma ile bu akımların önde gelenlerinden Rasyonalizm ve Empirizmin kurucularında Rene DESCARTES ve John LOCKE'un zihin anlayışları kıyaslanmıştır. Rasyonalizm ve Descartes insan bilgisinin temelinin zihin olduğunu savunurlar. Descartes zihnin, doğuştan gelen birtakım bilgiler üzerine, çeşitli çıkarımlar yaparak yeni bilgiler edindiğini söylüyor. Empirizm ve Locke ise insan bilgisinin temelinin duyum ve deneyim olduğunu savunurlar. Locke doğuştan gelen bilgileri reddeder, ona göre zihin, bilgilerini duyum ve deneyimden alır. Her iki filozof; deneyin bilgi kaynağı olduğu, ideler, Tanrı, ruh ve cisimlerin varlığı konularında ortak fikirlere sahiplerken, bunların algılanmaları ve yapıları hakkında farklı fikirlere sahiptirler. Human is abeing who thinks and has a mind. He is different from the other living beings from this view. What the mind is and how it works are the questions which have been argued since beginning of mankind and especially the ancient times in philosophy. Thanks to this, different ideologies have been formed through history of philosophy, and mankind was involved in them. İn this work, the mind comprehensions of Rene DESCARTES and John LOCKE, who are the founders of Rationalism and Empiricism, which are the pioneers of these ideologies, are compared. Rationalism and Rene DESCARTES believe that the fundamentals of human knowledge isthe mind. DESCARTES says that the mind adds new knowledge to the perception, which is inborn, by inferencing understandings. Empiricism and LOCKE accept that it is the sense and experiencce which are the essentials of human wisdom. LOCKE opposes the inborn understandings, according to him, mind acquires its knowledge from sense and experience. Both of the philosophers share the same opinions; they think experience is the source of knowledge and believe in the existence of ideas, the God, soul, and objects, whilst diverging about the comprehensions and structure of them.
Keywords: Felsefe; Felsefe, İslam